Pengaruh Job Embeddedness Dan Work Engagement Terhadap Intensi Turnover - Ayu Lestari; Mulia Sari Dewi (‎‎‎TAZKIYA Journal of Psychology, 2015)
Human resources is a major asset that can support the achievement of company objectives. Therefore, the company continually strives to develop and maintain employees in order not to affect the movement of employees (turnover). This study aims to examine the effect of job embeddedness and workengagement on turnover intention. These samples included 200 employees of PT Medco E & P Indonesia taken with nonprobability sampling technique. Test the validity of the instrument turnover intention, scale job embeddedness, and Utrecht Work Engagement Scale (Uwes) was done by using confirmatory factor analysis (CFA). Results of multiple regression analysis is that there is significant influence job embeddedness and work engagement against turnover intention with R = 0.43. There are two dimensions of job embeddedness of variables that provide significant and negative effect terhadapintensi turnover, the fit organization and sacrifice organization DOI: 10.15408/tazkiya.v20i2.9171